Metal transfer mapping for FCAW process by using near-infrared filming - Kordi, Hamed Alinezhad (2016)
In the Flux Cored Arc Welding (FCAW) process, the transfer of filler metal (metal transfer modes) to the base material to accomplish the weld bead determines the weld quality and therefore studies of such phenomena is demanded. Thus, in this work, the metal transfer through the FCAW process is investigated by filming the phenomena with the assist of near infrared visualization. During the literature survey, it was found that this technic has not been used so far for analyzing the FCAW process. It must be pointed out that the radiation emitted from the weld arc, fumes and particles (spattering) in this process represent a barrier for these studies based in the process visualization. The monitoring of metal transfer for FCAW process was carried out within the operational envelope of voltage and wire feed speed with the electrode E71T-1 (1.2 mm diameter) and Ar+25%CO2 as a shielding gas. A local developed near infrared filming with frame rate of 300 Hz was employed for metal transfer visualization in order to contribute to a better understanding of this process and evaluating characteristics of metal transfer, unlike previous studies, which used shadowgraph technique. It can clearly be seen how the droplet is created and transferred in this process and also identify the different modes of metal transfer by changing the parameters of voltage and wire feed speed in metal transfer maps. The final result of this study is the metal transfer mode maps, which establish suitable conditions and provide the basis for developing arc control strategies for the FCAW process.